Current Approaches to Improve Balance in Down Syndrome Population-A Systematic Review - Adeeb, Nazia; Farooqui, Sumaira Imran; Khan, Abid; Rizvi, Jaza; Kazmi, Syed Abid Mehdi (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Down syndrome is one of the most common chromosomal disorders in pediatrics characterized by variable intellectual disability, generalized joint laxity, and hypotonia that compromises their function and causes a delay in developing gross motor skills, poor balance, and coordination. Thus, this study aims to determine the current yet effective treatment approaches to improve balance in the Down syndrome population. The studies were explored across seven electronic databases that include MEDLINE, PubMed, Cochrane Library, Google Scholar, Scopus, PEDro, and Web of Science from inception till October 2020 comprised of experimental studies published in English language investigating the effects on balance in children and adults diagnosed with DS considering different interventions. A total of 1,570 records were retrieved from seven electronic databases published between the year's tenure of 2013-2020. 144 full-text papers were extracted to be reviewed, of which only 18 experimental studies were selected on the basis of inclusion criteria that involved 493 Down syndrome patients, investigated the effects of therapeutic exercises, manual therapy techniques, and patient-related instructions on standardized balance scales/tests. It was concluded that all the included trials demonstrated significantly profound effects in improving the static and dynamic balance of Down syndrome patients. Therefore, none of the interventions is declared as superior to another in terms of obtained results. Furthermore, these diverse interventions need to be investigated more for better understating and generalizability of outcomes.